Histological description of the bornean horned frog Megophrys nasuta (Amphibia: Anura: Megophryidae) skin structure from different body regions - Ramlah, Zainudin; Elvy Quatrin, Deka; Dayangku Norlida, Awang Ojep; Lela, Suut; Aida Shafreena, Ahmad Puad; Mohd Azlan, Jayasilan; Ahmad Hata, Rasit (Malaysian Society of Applied Biology, 2018)
Skin is the first protection barrier for the frog species that protect them from high temperature, chemical toxics, and over exposure to sunlight. Thus variation in skin characteristics might reflect their adaptation to environment. Since leaf litter frogs are facing threats of habitat fragmentation, we investigate the skin structure of the Bornean leaf litter horned frog Megophrys nasuta, from different body regions. Histological analysis of the frog skins and slide preparations using Haematoxylin and Eosin staining protocol were employed. Findings indicated that all body regions of M. nasuta skins have similar characteristics of the strata, epidermis and dermis layers. However, thickness of the epidermis layer and glands distribution varies between dorsal and ventral (areas that were first in contact with the environment) thus suggesting their adaptation strategy. The observed distributions of serous and mucous glands on different skin regions might also reflect the habit of this species in their natural habitat. These results may help in understanding the function of the skin structure to meet their ecological needs especially in the changing environment at fragmented area. The data should be extended and explored to study the effects of habitat fragmentation on the amphibians.